A 6-b 12-GSamples - Jaesik Lee (IEEE Journal of solid state circuits)
This paper presents a 6-b 12-GSample/s track-and-hold amplifier (THA) fabricated in an InP-InGaAs-InP double heterojunction bipolar transistor (DHBT) technology. The THA is intended for the front end of a high-speed analog-to-digital converter in a digital-based electronic polarization-mode dispersion compensation circuit for a 10-Gb/s optical receiver. With a high-speed switched emitter follower and clocked track-to-hold transition operation, it shows the signal bandwidth over 14 GHz and features a total harmonic distortion (THD) compatible with 6-b operation with input frequency of 6 GHz and a sampling frequency of 12 GHz. The THD increases better than -23 dB with a 12-GHz input signal of 1 Vpp, corresponding to a 4-b resolution, under a differential clock of 12 GHz.